2003
DOI: 10.1071/sr01090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil type, exchangeable sodium percentage, water content, and organic amendments on urea hydrolysis in some tropical Indian soils

Abstract: Urea has emerged as one of the most extensively used sources of nitrogen fertiliser in recent years because of its low cost per unit nitrogen. Urea hydrolysis in soils is an enzymatic decomposition process by the enzyme urease. The effects of soil type, exchangeable sodium percentage, moisture regime, and organic manures and their levels on the kinetics of urea hydrolysis were studied in a series of laboratory incubation experiments at 25 ± 1�C. Urea transformation followed first-order kinetics, and the first-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…These results may be due to a higher degree of urea hydrolysis at field capacity. Similar results were reported by Savant et al, (1985), Singh andSingh (1996), andWali et al, (2003) in which the rate of urea hydrolysis was determined to be higher at field capacity as compared to saturated conditions because regulated oxygen diffusion under field capacity conditions maximizes the urease activity in the soil.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These results may be due to a higher degree of urea hydrolysis at field capacity. Similar results were reported by Savant et al, (1985), Singh andSingh (1996), andWali et al, (2003) in which the rate of urea hydrolysis was determined to be higher at field capacity as compared to saturated conditions because regulated oxygen diffusion under field capacity conditions maximizes the urease activity in the soil.…”
Section: Resultssupporting
confidence: 89%
“…Leaching experiments in soil columns have demonstrated that urea moves through soil with irrigation water depending on the rate of water application (Antil et al, 1992). It has been found that the rate of urea hydrolysis was slow in saturated soils as compared to field capacity (Wali et al, 2003) and occurred at a higher rate at 40% versus 60% water-holding capacity (Sankhayan and Shukla, 1976). Information on the influence of crop residue additions and organic manures on urea hydrolysis in relation to applied water is limited.…”
mentioning
confidence: 97%
“…The hydrolysis of urea followed first order kinetics upto the first 24 h (see Figure 1). Kumar and Wagenet (1984) and Wali et al (2003) found that rate of urea hydrolysis in different soils followed first order kinetics and values of first order rate constant varied from 0.032 in Balsamand sand to 0.118 h 71 in Gulkani clay loam.…”
Section: Resultsmentioning
confidence: 98%
“…Urea is readily hydrolyzed to ammonium carbonate by the enzyme urease. The rate of hydrolysis to ammonium and loss from volatilization in the form of ammonia depends on the timing of application, weather, soil temperature and pH and other factors (Khakural and Alva 1995;Wali et al 2003). These losses may exceed 20%, even 40% depending on pH ( Figure 2).…”
Section: Natural and Anthropogenic Enrichment Of Urea In Coastal Watersmentioning
confidence: 96%